Antibacterial, antifungal and antioxidant activities of the ethanol extract of the stem bark of Clausena heptaphylla - Fakruddin Md; Mannan Khanjada Shahnewaj; Mazumdar Reaz; Afroz Hafsa (BMC, 2012)
Abstract Background There is wide spread interest in drugs derived from plants as green medicine is believed to be safe and dependable, compared with costly synthetic drugs that have adverse effects. Methods We have attempted to evaluate the antioxidant, In vitro thrombolytic, antibacterial, antifungal and cytotoxic effects of Clausena heptaphylla (Rutaceae) stem bark extract ethanol extract. Results Ethanolic stem bark extract of Clausena heptaphylla (CHET) contains flavonoids, alkaloids, saponins and steroids but it lacks tannins, anthraquinones and resins. Phenol content of the extract was 13.42 mg/g and flavonoid content was 68.9 mg/g. CHET exhibited significant DPPH free radical scavenging activity with IC50 value of 3.11 μg/ml. Reducing power of CHET was also moderately stronger. In the cytotoxicity assay, LC50 and Chi-square value of the ethanolic extract against brine shrimp nauplii were 144.1461 μg/ml and 0.8533 demonstrating potent cytotoxic effect of the extract. In vitro thrombolytic activity of CHET is significant with 45.38% clot lysis capability compared to that of Streptokinase (65.78%). In antibacterial screening, moderate zone of inhibition (6.5-9.0 mm in diameter) was observed against gram-positive Bacillus subtilis ATCC 11774, Bacillus cereus ATCC 10876, Staphylococcus aureus ATCC 25923, Bacillus polymyxa ATCC 842 and Bacillus megaterium ATCC 13578 and less promising zone of inhibition (3.0-4.5 mm in diameter) against gram-negative Salmonella typhi ATCC 65154, Shigella flexneri ATCC 12022, Proteus vulgaris ATCC 13315 and Escherichia coli ATCC 25922. Shigella sonnei ATCC 8992 did not show any sensitivity. The MIC values against these bacteria were ranged from 2,000 to 3,500 μg/ml. The extract showed significant zone of inhibition against Rhizopus oryzae DSM 2200, Aspergillus niger DSM 737 and Aspergillus ochraceus DSM 824 in antifungal assay. Conclusions Further advanced research is necessary to isolate and characterize the chemical components responsible for the therapeutic properties of the plant.